Evaluating the readability, quality and reliability of online information on Behçet’s disease - Özduran, E.; Hanci, V. (Reumatismo, 2022)
There are concerns over the reliability and comprehensibility of health-related information on the internet. The goal of our research was to analyze the readability, reliability, and quality of information obtained from websites associated with Behçet’s disease (BD). On September 20, 2021, the term BD was used to perform a search on Google, and 100 eligible websites were identified. The Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level (FKGL), and Gunning Fog (GFOG) were used to evaluate the readability of the website. The JAMA score was used to assess the websites’ reliability, the DISCERN score and the Health on the Net Foundation code of conduct (HONcode) were used to assess quality, and Alexa was used to analyze their popularity. Sections of the text were evaluated, and the results revealed that the mean FRES was 35.49±14.42 (difficult) and the mean GFOG was 14.93±3.13 years (very difficult). According to the JAMA scores, 36% of the websites had a high reliability rating and 20% adhered to the HONcode. The readability was found to significantly differ from the reliability of the websites (p